2004
DOI: 10.1007/s00213-003-1688-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the endogenous ? opioid agonist dynorphin A(1?17) on cocaine-evoked increases in striatal dopamine levels and cocaine-induced place preference in C57BL/6J mice

Abstract: The blockade of the cocaine-induced rise in striatal dopamine may contribute to both dynorphin's ability to prevent the development of cocaine-induced conditioned place preference and to attenuate the increase in locomotor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 37 publications
7
92
0
Order By: Relevance
“…S6). Pretreatment with Dyn A (1-17) is effective in decreasing striatal DA neurotransmission and attenuating cocaine-induced CPP in mice (34). Overexpression of CREB with resulting increases in ppDyn gene expression in the NAc has been shown to decrease the rewarding effects of cocaine (29).…”
Section: Discussionmentioning
confidence: 99%
“…S6). Pretreatment with Dyn A (1-17) is effective in decreasing striatal DA neurotransmission and attenuating cocaine-induced CPP in mice (34). Overexpression of CREB with resulting increases in ppDyn gene expression in the NAc has been shown to decrease the rewarding effects of cocaine (29).…”
Section: Discussionmentioning
confidence: 99%
“…Central infusion of dynorphin A(1-17) prevents the development of cocaine-induced CPP (Zhang et al, 2004), and kappa opioid receptor (KOP-r) agonists elevate the ICSS threshold in the LH (Todtenkopf et al, 2004). The ppDyn gene is co-expressed in most LH orexin neurons (Chou et al, 2001) and dynorphin A (1-13) has regulatory effects on the orexin system (Li and van den Pol, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas TRPM8 activation by cold as well as by exogenous substances such as menthol have been the matter of extensive studies (Almaraz et al, 2014), endogenous activators or inhibitors of TRPM8 have more rarely been identified. Interestingly, it was shown previously that androgens increase TRPM8 expression in non-neural cells (L. Zhang and Barritt, 2004;Thebault et al, 2005). In addition to this genomic regulation by androgens, testosterone acts directly on the TRPM8 channel at subphysiological concentrations (Asuthkar et al, 2015), and recent unpublished work also shows that, in the presence of the androgen receptor, physiological concentration of testosterone specifically inhibits TRPM8 activity in transfected cells and primary sensory neurons through direct interaction of the channel with the androgen receptor at the plasma membrane.…”
mentioning
confidence: 90%